2018
DOI: 10.3389/fpsyg.2017.02251
|View full text |Cite
|
Sign up to set email alerts
|

The Comprehension of Familiar and Novel Metaphoric Meanings in Schizophrenia: A Pilot Study

Abstract: Miscomprehension of nonliteral (“figurative”) language like metaphors, proverbs, idioms, and ironic expressions by patients with schizophrenia is a phenomenon mentioned already in historical psychiatric descriptions. However, it was only recently that studies did differentiate between novel and conventional metaphors, a factor that is known to influence the difficulty of comprehension in healthy subjects. Further, familiarity with stimuli is an important factor for comprehension, which was not recommended in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 101 publications
(153 reference statements)
3
15
0
1
Order By: Relevance
“…Of note, the different tasks may each have advantages, but at the same time they can impede comprehension if inappropriately used with individuals with ASD. For instance, multiple-choice tasks can be desirable from the psychometric perspective due to an easy and precise scoring (Rapp et al, 2018) and high reliability (see, for instance, the different reliability values of figurative language tasks-multiple choice vs. verbal explanation in Carotenuto et al, 2018). In contrast, multiple-choice tasks are more susceptible for measurement error due to the possibility of guessing the responses (Kline, 2009), as well as due to tapping more executive functions because of the need to inhibit the incorrect alternatives and select the correct one.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, the different tasks may each have advantages, but at the same time they can impede comprehension if inappropriately used with individuals with ASD. For instance, multiple-choice tasks can be desirable from the psychometric perspective due to an easy and precise scoring (Rapp et al, 2018) and high reliability (see, for instance, the different reliability values of figurative language tasks-multiple choice vs. verbal explanation in Carotenuto et al, 2018). In contrast, multiple-choice tasks are more susceptible for measurement error due to the possibility of guessing the responses (Kline, 2009), as well as due to tapping more executive functions because of the need to inhibit the incorrect alternatives and select the correct one.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, multiple-choice tasks do not rely on expressive language or meta-linguistic skills and require minimal social interaction with the examiner. However, multiple-choice tasks might be more costly in terms of need for inhibiting the false alternative(s) and selecting the correct one, as suggested by evidence from patients with brain lesions (Rapp, Felsenheimer, Langohr, & Klupp, 2018). The important role of the response format in metaphor comprehension is also supported by studies explicitly comparing different tasks.…”
Section: Response Formatmentioning
confidence: 99%
See 1 more Smart Citation
“…Auch wenn hier gezielt ein Screeningverfahren gewählt wurde, müsste zwecks Optimierung der Reliabilität allenfalls die Sprichwortliste von Barth und Küfferle [28] herangezogen werden; umfasst diese doch 14 Items. Zudem müsste kontrolliert werden, ob die präsentierten Sprichwörter für den Patienten als solche neuartig sind und dadurch einen kognitiven Prozess des Abstrahierens respektive Inhibierens verlangen oder bekannt sind und somit lediglich die Decodierung von erworbenem expliziten Wissen erfordern [29,30].…”
Section: Diskussionunclassified
“…SZ patients have more difficulty understanding conventional metaphors than do healthy individuals (1,(12)(13)(14); they exhibit difficulty giving verbal explanations of metaphors and make a significantly higher number of literal incorrect (giving the literal meaning of words) and abstract incorrect (giving an answer that is abstract, but not in line with the meaning of the metaphor) errors than individuals without SZ (15). A study by Mossaheb et al (16) showed that processing metaphors may be related to processing speed, cognitive flexibility, and a range of intelligence quotient (IQ) subtests.…”
Section: Introductionmentioning
confidence: 99%